Pengaruh Influencer Marketing, Brand Image, dan Kualitas produk Terhadap Keputusan Pembelian Produk Fashion Lokal di Platfrom Tiktokshop - Zahrotul Wahyu Layyinah; Misti Hariasih; Mas Oetarjo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of digital technology and social media has changed the way people buy goods and how companies advertise. One method frequently used is influencer marketing, which is promotion through people with large social media followers to persuade people to buy goods. This phenomenon has become increasingly popular due to the TikTok Shop feature, which has become a place for local brands to sell products, especially to the younger generation. This study aims to observe and analyze the impact of brand image, influencer marketing, and product quality on the decision to purchase local fashion products on TikTok Shop. The method used is quantitative research by sending questionnaires to 100 people in Sidoarjo who have purchased local fashion products through TikTok Shop. The sampling technique used is purposive sampling. Data were analyzed using validity and reliability tests, followed by classical assumption tests, multiple linear regression tests, T-tests, and coefficient of determination tests using the SPSS version 26 program. The results of this study show that the three factors: influencer marketing, brand image, and product quality have a positive and significant influence on purchasing decisions. These findings demonstrate that the right digital marketing strategy, a strong brand image, and high-quality products can boost purchasing power and increase the competitiveness of local brands in the digital era.